Temporal and Microspatial Heterogeneity in Transmission Dynamics of Coendemic Plasmodium vivax and Plasmodium falciparum in Two Rural Cohort Populations in the Peruvian Amazon. (21st August 2020) - Rosas-Aguirre, Angel; Guzman-Guzman, Mitchel; Chuquiyauri, Raul; Moreno, Marta; Manrique, Paulo; Ramirez, Roberson; Carrasco-Escobar, Gabriel; Rodriguez, Hugo; Speybroeck, Niko; Conn, Jan E; Gamboa, Dionicia; Vinetz, Joseph M; et al.
Abstract: Background: Malaria is highly heterogeneous: its changing malaria microepidemiology needs to be addressed to support malaria elimination efforts at the regional level. Methods: A 3-year, population-based cohort study in 2 settings in the Peruvian Amazon (Lupuna, Cahuide) followed participants by passive and active case detection from January 2013 to December 2015. Incidence and prevalence rates were estimated using microscopy and polymerase chain reaction (PCR). Results: Lupuna registered 1828 infections (1708 Plasmodium vivax, 120 Plasmodium falciparum ; incidence was 80.7 infections/100 person-years (95% confidence interval [CI], 77.1–84.5). Cahuide detected 1046 infections (1024 P vivax, 20 P falciparum, 2 mixed); incidence was 40.2 infections/100 person-years (95% CI, 37.9–42.7). Recurrent P vivax infections predominated onwards from 2013. According to PCR data, submicroscopic predominated over microscopic infections, especially in periods of low transmission. The integration of parasitological, entomological, and environmental observations evidenced an intense and seasonal transmission resilient to standard control measures in Lupuna and a persistent residual transmission after severe outbreaks were intensively handled in Cahuide. Conclusions: In 2 exemplars of complex local malaria transmission, standard control strategies failed to eliminate submicroscopic and hypnozoite reservoirs, enabling persistent transmission. Abstract : This intensive 3-year population-based cohort study in 2 contrasting settings in the Peruvian Amazon demonstrated the complexity of P falciparum and P vivax coendemicity, driven by the complex interplay of human behavior, parasite biology, and environmental determinants of mosquito prevalence.